The Influence of Interest in Learning English for Students Outside the English Language Study Program (Case Study of Islamic Education Management Study Program) - Jumarah, Jumarah (FAKULTAS TARBIYAH, 2022)
The purpose of this study was to identify the factors that influence the learning interest of non-English speaking students of the MPI STIT Wali Jerowaru study program. It also aims to evaluate which motivational subfactors have more influence on student learning. This study used a qualitative research method by including a questionnaire consisting of 2 intrinsic motivation factors and 3 extrinsic motivation factors. Data from the questionnaire were analyzed using statistical procedures and described descriptively. Thus, these results provide implications about what must be considered in language learning. especially in learning English. Therefore, the quality of lecturers and learning facilities needs to be improved because it will increase student motivation in learning language.